2014
DOI: 10.3329/jles.v8i0.20139
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Flag Leaf with Yield in Several Rice Cultivars

Abstract: Abstract:The uppermost leaf below the panicle is the flag leaf that provides the most important source of photosynthetic energy during reproduction and grain filling, thereby has great impact in panicle development and grain yield in rice. In the present investigation in order to explore the relationship between grain yield and flag leaf parameters, yield composition, length and width of the flag leaf, and panicle length were measured in some rice cultivars. Statistical analysis indicated that flag leaf length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
5
19
0
1
Order By: Relevance
“…This is an important leaf structural trait, which determines the yield capacity of rice. It is positively correlated with PN largely because of a high Chl content in thicker leaves (Rahman et al 2013). Our results showed significant positive associa tion of leaf thickness with PN in both populations.…”
Section: Marker-trait Associationsupporting
confidence: 57%
See 1 more Smart Citation
“…This is an important leaf structural trait, which determines the yield capacity of rice. It is positively correlated with PN largely because of a high Chl content in thicker leaves (Rahman et al 2013). Our results showed significant positive associa tion of leaf thickness with PN in both populations.…”
Section: Marker-trait Associationsupporting
confidence: 57%
“…There is a significant positive association between leaf structural traits and physiological traits (Giuliani et al 2013). In general, leaf thickness has a positive association with photosynthesis because of a high Chl content in thicker leaves (Rahman et al 2013) that directly affects the crop biomass (Shen 1980, Chen et al 1995 and grain yield (Xu and Shen 1994). Unlike stomata, mesophyll is also an important decisive factor in rice photosynthesis as 90% of chloroplasts are located there.…”
Section: Introductionmentioning
confidence: 99%
“…The interrelationships of plant height, days to flowering, and day to maturity with the grains per panicle showed a negative direct effect while tillers per hill and flag leaf length to width ratio showed a positive direct effect ( Table 4 ). It was reported by Rahman et al [ 19 ] that the flag leaf area was directly related to the yield components. Also, flag leaves play a significant role in enhancing rice yield because these leaves remain the only source of assimilating during the grain filling stage [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plant leaf is an important organ of photosynthesis. In particular, the uppermost flag leaf has a crucial role in supplying photosynthates to the developing grains [ 27 , 28 ]. Previous studies have demonstrated that grain yield characteristics are positively correlated with flag leaf traits [ 29 ].…”
Section: Discussionmentioning
confidence: 99%